Medium of Instruction Policies: Which Agenda? Whose Agenda? - Tollefson, James W.; Tsui, Amy B. M. (Routledge, 2004)
Medium of instruction policies in education have considerable impact not only on the school performance of students and the daily work of teachers, but also on various forms of social and economic (in)equality. In many multiethnic and multilingual countries, the choice of a language for the medium of instruction in state educational systems raises a fundamental and complex educational question: what combination of instruction in students' native language(s) and in a second language of wider communication will ensure that students gain both effective subject-content education, as well as the second-language skills necessary for higher education and employment? Beyond this educational issue of choice of language(s) of instruction, medium of instruction policies are also linked to a range of important sociopolitical issues, including globalization, migration, labor policy, elite competition, and the distribution of economic resources and political power. The contributors to this volume examine the tension between the educational agendas and other social and political agendas underlying medium of instruction policies in different countries around the world, and unravel the connections between these policies and the related, critically important educational, social, political, and economic issues. Medium of Instruction Policies: Which Agenda? Whose Agenda? is intended for scholars and specialists in education, language policy, sociolinguistics, applied linguistics, and language teaching, and is intended for use in graduate and advanced undergraduate courses on language education and language policy. Contents: Preface. A.B.M. Tsui, J.W. Tollefson, The Centrality of Medium-of-Instruction Policy in Sociopolitical Processes. Part I: Minority Languages in English-Dominant States. S. May, Maori-Medium Education in Aotearoa/New Zealand. D.V. Jones, M. Martin-Jones, Bilingual Education and Language Revitalization in Wales: Past Achievements and Current Issues. T.L. McCarty, Dangerous Difference: A Critical-Historical Analysis of Language Education Policies in the United States. Part II: Language in Post-Colonial States. A.B.M. Tsui, Medium of Instruction in Hong Kong: One Country, Two Systems, Whose Language? A. Pakir, Medium-of-Instruction Policy in Singapore. S.K. Gill, Medium-of-Instruction Policy in Higher Education in Malaysia: Nationalism Versus Internationalization. I. Nical, J.J. Smolicz, M.J. Secombe, Rural Students and the Philippine Bilingual Education Program on the Island of Leyte. E. Annamalai, Medium of Power: The Question of English in Education in India. H. Alidou, Medium of Instruction in Post-Colonial Africa. Part III: Managing and Exploiting Language Conflict. V. Webb, Language Policy in Post-Apartheid South Africa. K.A. King, C. Benson, Indigenous Language Education in Bolivia and Ecuador: Contexts, Changes, and Challenges. J.W. Tollefson, Medium of Instruction in Slovenia: European Integration and Ethnolinguistic Nationalism. J.W. Tollefson, A.B.M. Tsui, Contexts of Medium-of-Instruction Policy.